THE APPLICATION OF PRINCIPAL COMPONENT ANALYSIS (PCA) FOR THE STUDY OF THE SPANISH TOURIST DEMAND - González, María Jesús González; Pascual, María-Eva Vallejo (Quaestiones Geographicae, 2018)
The objective of this study is the characterisation of the Spanish autonomous communities as tourist destinations for Spanish trips, based on the activities carried out, using the principal component method. The Spanish tourist is not only motivated by the sun and beach. This paper aims to clarify how Spanish people consider other tourist destinations. We contrast how frequently other types of tourism are valued when choosing their destination within the Spanish geography. Inland tourism, sports tourism, entertainment as well as gastronomy are becoming increasingly important.